A novel selenoalkenyl-isoxazole based donor–acceptor nonlinear optical material. Issue 1 (8th December 2017) - Holzer, Brigitte; Stöger, Berthold; Kautny, Paul; Reider, Georg; Hametner, Christian; Fröhlich, Johannes; Lumpi, Daniel
Abstract : A novel selenium-based donor–acceptor molecule with high second harmonic generation efficiency is presented. Abstract : The structure property relationships of untwinned enantiomorphic Z -(methylseleno)alkenyl-substituted phenyl-isoxazole and its isostructural triazole congener both crystallizing in the P 21 21 21 space group were investigated with respect to UV/vis absorption, thermal behaviour, and second harmonic generation ability. Differential scanning calorimetry revealed a significantly higher melting point of the novel isoxazole compound compared to the triazole derivative and therefore a broader thermal application window. The SHG efficiency of the isoxazole derivative is approximately two thirds the value of the triazole compound and approximately 27 times higher than potassium dihydrogen phosphate. Thus, the developed molecular scaffold represents an interesting novel type of nonlinear optical (NLO) chromophore.